Synergy, Salary, and Satisfaction: Benefits of Training in Critical Care Medicine and Infectious Diseases Gleaned From a National Pilot Survey of Dually Trained Physicians - Kadri, Sameer S. (Clin Infect Dis, 2016)
Background. An increasing number of physicians are seeking dual training in critical care medicine (CCM) and infectious diseases (ID). Understanding experiences and perceptions of CCM-ID physicians could inform career choices and programmatic innovation. Methods. All physicians trained and/or certified in both CCM and ID to date in the United States were sent a Web-based questionnaire in 2015. Responses enabled a cross-sectional analysis of physician demographics and training and practice characteristics and satisfaction. Results. Of 202 CCM-ID physicians, 196 were alive and reachable. The response rate was 79%. Forty-six percent trained and 34% practice in the northeastern United States. Only 40% received dual training at the same institution. Eighty-three percent identified as either an intensivist with ID expertise (44%) or as equally an intensivist and ID physician (38%). Median salary was $265 000 (interquartile range [IQR], $215 000–$350 000). Practice settings were split between academic (45%) and community settings (42%). Two-thirds are clinicians but 62% conduct some research and 26% practice outpatient ID. Top reasons to dually specialize included clinical synergy (70%), procedural activity (50%), and less interest in pulmonology (49%). Although 38% cited less proficiency with bronchoscopy as a disadvantage, 87% seldom need pulmonary consultation in the intensive care unit. Median career satisfaction was 4 (IQR, 4–5) out of 5, and 76% would dually train again. Conclusions. CCM-ID graduates prefer the acute care setting, predominantly CCM or a combination of CCM and ID. They find combination training and practice to be synergistic and satisfying, but most have had to seek CCM and ID training independently at separate institutions. Given these findings, avenues for combined training in CCM-ID should be considered.